2020
DOI: 10.1002/ece3.6749
|View full text |Cite
|
Sign up to set email alerts
|

The insertion of a mitochondrial selfish element into the nuclear genome and its consequences

Abstract: Homing endonucleases (HE) are enzymes capable of cutting DNA at highly specific target sequences, the repair of the generated double‐strand break resulting in the insertion of the HE‐encoding gene (“homing” mechanism). HEs are present in all three domains of life and viruses; in eukaryotes, they are mostly found in the genomes of mitochondria and chloroplasts, as well as nuclear ribosomal RNAs. We here report the case of a HE that accidentally integrated into a telomeric region of the nuclear genome of the fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 77 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…Bioinformatic analysis of Kala et al (2014) revealed that the role of HNH proteins in terminase function is widespread among long-tailed phages and is uniquely required for the activity of the Terminase1 family of large terminase proteins. HEGs, encoding endonucleases capable of cutting site-specific DNA that promotes the lateral transfer of their own, can themselves be mobile elements moving independently ( Mota and Collins, 1988 ; Stoddard, 2005 ; Buttimer et al, 2020 ; Dutheil et al, 2020 ). Mobile genetic elements have the potential to influence the expression of genes surrounding their insertion site upon invasion of a genome ( Gibb and Edgell, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic analysis of Kala et al (2014) revealed that the role of HNH proteins in terminase function is widespread among long-tailed phages and is uniquely required for the activity of the Terminase1 family of large terminase proteins. HEGs, encoding endonucleases capable of cutting site-specific DNA that promotes the lateral transfer of their own, can themselves be mobile elements moving independently ( Mota and Collins, 1988 ; Stoddard, 2005 ; Buttimer et al, 2020 ; Dutheil et al, 2020 ). Mobile genetic elements have the potential to influence the expression of genes surrounding their insertion site upon invasion of a genome ( Gibb and Edgell, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…UTASb is near telomere repeats or 5’ upstream of UTASa. UTASb may be a truncated segment generated from the homing endonuclease gene HEG [ 43 ]. UTASb consists of a highly conserved “core” sequence, an OrsD domain, or both [ 42 ].…”
Section: Resultsmentioning
confidence: 99%